Contribution of Comorbidities in Mortality of COVID-19 Patients Admitted to Tertiary Care Center: A Descriptive Cross-sectional Study - Bhandari, Nirajan; KC, Rupak; Paudel, Neetika; Chaulagain, Pratima; Singh, Pankaj Kumar; Pandey, Ravi (Journal of Institute of Medicine Nepal, 2024)
Introduction The majority of COVID patients with comorbidity were admitted to Intensive Care for treatment, and their outcomes were poor, necessitating the need for this study to determine the mortality due to comorbidities. This study aimed to find out the prevalence of comorbidities in COVID-19 mortality cases recorded in the tertiary hospital. Methods Cases with comorbidities among 162 cases of deaths due to COVID-19 were assessed in this retrospective cross-sectional study. Data were obtained from the Department of Biostatistics. Age, sex and comorbidity status were recorded in each mortality case. Ethical approval was obtained from the Institutional Review Committee. Results Out of 162 mortality cases, 62 (38.27%) patients had comorbidity. Among 62 mortality cases with ages ranging from 26-80 years and mean age was found to be 57.26 ± 11.18. Our data included a total of 41 (66.20%) males and 21 (33.80%) females. Diabetes with hypertension (23%) was the leading comorbidity in the COVID mortality case followed by hypertension (20%), diabetes (18%), chronic kidney disease (12%), hypothyroidism (9%), and other cases (18%). Other cases include upper gastrointestinal (UGI) bleeding, hepatic encephalopathy, old cerebrovascular accidents (CVA), liver abscess, and other surgical cases. Conclusion Diabetes with hypertension was the major comorbidity in COVID-19 mortality.